(3GdQSGdI GdecfjI aj GdOhGA HGdcfjIs - (3MSjf Hf Ydj Hf SdjeGf GdMfaj, MSjf NhLI,J (B1169 (3g` s ((3jhSa Hf eMeO GdRZhGfj s)
(3ChdgG (B:s
(3MeO Gdef CXgQ ef GdGSQGQ GdecfjI hHYO deG hbYJ GdGHUGQ aj QjGV GdWH GdMSGf s
(3BNQgG (B:s
(3adh dGYbhd GdfGS cGfhG HgG hdhdG dSGf GdeQA s
(3Vef eLehY , JQJjHgG (B: 5s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B609s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
(3GdfSNI HgG JdhjK s
Keywords: (3eJaQbGJs